Relationship between breast arterial calcification and coronary artery disease by invasive coronary angiography in postmenopausal women - Gardinalli-Filho, Gildo [UNESP] (2022)
Purpose: To evaluate the relationship between the presence of BAC and coronary artery disease (CAD) by invasive coronary angiography (ICA) in postmenopausal women. Methods: In this cross-sectional study, postmenopausal women (age ≥ 45 years) with history of CAD, who underwent both ICA and digitized mammography, within six months of each other, were enrolled. Women who underwent prior percutaneous coronary intervention, or exhibited grade D breast density (BI-RADS®) or breast cancer upon mammography were excluded. Digital mammograms were identified in the electronic medical record system and reviewed for the presence of BAC, without knowledge of the ICA results by two experienced physicians. The ICA results were obtained from the electronic medical record, and categorized as follows: 1-single-vessel disease; 2-two-vessel disease; and 3-multivessel disease (≥3vessels). For statistical analysis Student t test, Gamma distribution, Chi-square test and logistic regression (odds ratio,OR) were used. Results: Of the 183 postmenopausal women evaluated, 39 (21.3 %) had BAC. Women with BAC were older and had a longer time since menopause when compared to women without BAC (68.2 ± 9.6 × 59.6 ± 10.0 years of age and 19 ± 10.1 × 13.5 ± 8.2 years, respectively) (p < 0.0.0001). Among the clinical and cardiovascular characteristics evaluated, only the incidence of smoking was higher in women with BAC (p = 0.007). There was no difference in the number of affected vessels upon ICA in women with or without BAC (p = 0.683). In multivariate analysis, after adjustment for age, time since menopause and smoking, the presence of BAC was not associated with a significant risk of observing a greater number of affected vessels upon ICA (OR1.07; 95 %CI 0.41–2.76, p = 0.609). Conclusions: The presence of BAC was not associated with the severity of CAD in postmenopausal women.